The Development of Virtual Reality-Based Physics Learning Media on Kepler’s Law Topic - Ma'ruf Ma'ruf; Ana Dhiqfaini Sultan; Suci Haerunnisa (Journal of Mathematics Science and Computer Education, 2024)
This study aimed to determine the validity and practicality of virtual reality-based physics learning media on the topic of Kepler's laws. The number of participants in this research was 32 students and two teachers. The research method used was the R&D research method and the ADDIE approach. Data analysis was conducted using the Gregory test and the results of the data analysis. The virtual reality-based physics learning media on the topic of Kepler's laws has high content validity, with an average score of 0.97, and the results show that both the teachers and students had a high level of cognitive, affective, and conative responses to the VR-based learning medium. The average cognitive response was 80%, the average affective response was 85%, and the average conative response was 80%. Overall, the high level of response from the teachers and students suggests that the VR-based learning medium is practical for teaching Kepler's laws to physics students. These results demonstrate that the virtual reality-based learning medium is an effective tool for teaching and learning about Kepler's laws interactively and visually.